Applying real life examples for improved learning outcomes - Löbmann, Korbinian (Improving University Science Teaching and Learning, 2023)
The aim of this project was to redesign and optimize a classroom lesson within the course “Drug Formulation” for BSc students in pharmacy by applying a ‘problem to solve’ teaching style in order to improve the students ability to apply and crosslink their knowledge about pharmaceutical formulations, i.e. support deeper learning and understanding rather than memory.